Additional Sodium Insertion into Polyanionic Cathodes for Higher‐Energy Na‐Ion Batteries. Issue 18 (16th May 2017) - Bianchini, Matteo; Xiao, Penghao; Wang, Yan; Ceder, Gerbrand
Abstract : Na‐ion technology is increasingly studied as a low‐cost solution for grid storage applications. Many positive electrode materials have been reported, mainly among layered oxides and polyanionic compounds. The vanadium oxy/flurophosphate solid solution Na3 V2 (PO4 )2 F3‐ y O2 y (0 ≤ y ≤ 1), in particular, has proven the ability to deliver ≈500 Wh kg ‐1, operating on the V 3+ /V 4+ ( y = 0) or V 4+ /V 5+ redox couples ( y = 1). This paper reports here on a significant increase in specific energy by enabling sodium insertion into Na3 V2 (PO4 )2 FO2 to reach Na4 V2 (PO4 )2 FO2 upon discharge. This occurs at ≈1.6 V and increases the theoretical specific energy to 600 Wh kg −1, rivaling that of several Li‐ion battery cathodes. This improvement is achieved by the judicious modification of the composition either as O for F substitution, or Al for V substitution, both of which disrupt Na‐ion ordering and thereby enable insertion of the 4th Na. This paper furthermore shows from operando X‐Ray Diffraction (XRD) that this energy is obtained in the cycling range Na4 V2 (PO4 )2 FO2 –NaV2 (PO4 )2 FO2 with a very small overall volume change of 1.7%, which is one of the smallest volume changes for Na‐ion cathodes and which is a crucial requisite for stable long‐term cycling. Abstract : The additional intercalation of sodium into polyanionic frameworks of the family Na3 V2 (PO4 )2 F3‐2 y O2 y is reported. The most oxygen‐rich compound, in particular, obtains extra capacity at a relatively high voltage and operando XRD demonstrates a low volume change upon cycling. Aluminum substitution is finally used into this framework to experimentally demonstrate how to improve sodium kinetics in this highly sodiated regime.